The teachers' makeup in the changing process of the pedagogical theories - Claudia Aparecida Sorgon Scotuzzi (Universidade Estadual Paulista Júlio de Mesquita Filho, 2012)
This article is a bibliographic review on the different pedagogical theories and their relation to the teachers' makeup. It presents the counterpoint between traditional school, based on the strength of models and the study of classics of human history, and the new school, which defends the idea of focusing on student's activity and methods and programs based on the child's experience. It adopts, for doing this, the following theoretical frame: Saviani (2008a/2008b), Snyders (1974), Gramsci (1991), Luzuriaga (1961), Bloch (1951), Hernandez (1998), Ball (1994), and Gauthier (1998), among others. It proposes a reflection on the school as the main education strategic resource of human communities and on the knowledge required to the teaching professionalization. It discusses, also, the pedagogies adopted by the State of Sao Paulo Education Bureau, in the last decades, including the new official syllabus, and the influence of the State and the market in the teaching practice.